Glass fiber supports modified by layers of silica and carbon nanofibers; Catalysis for Sustainable Energy; Vol. 4, iss. 1 - Popov М. V.; Zazhigalov S. V.; Larina Т. V.; Cherepanova S. V.; Bannov A. G.; Lopatin S. A.; Zagoruiko A. N. Andrey Nikolaevich (2017, 2017)
Title screen